Application of Qasam Rules in the Sūrah al-Syams (A Comparative Study Between the Tafsir Bahrul Muhith and Tafsir Mafatihul Ghoib) - Rus’anuddin Hasibuan; Zulheldi; Muhammad Irfan (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This study examines the theological, linguistic, and hermeneutical dimensions of Qasam (divine oaths) in Surah Al-Syams (Q. 91) through a comparative analysis of two classical exegeses: Tafsir Bahrul Muhith by Abu Hayyan al-Andalusi (a linguistic approach) and Tafsir Mafatihul Ghoib by Fakhruddin al-Razi (a philosophical-theological approach). The research addresses a gap in existing scholarship by systematically comparing how these methodologies interpret the Qasam verses (Q. 91:1–10) and their implications for understanding moral and cosmological messages. Using qualitative library research, the study applies Nasr Hamid Abu Zayd’s hermeneutics and ‘Ulum al-Qur’an theories on muqsam bih (oath objects) and muqsam ‘alayh (oath purposes). Findings reveal that Abu Hayyan emphasizes grammatical precision and historical context, while al-Razi prioritizes metaphysical and ethical reflections. Both, however, affirm the oath’s function in affirming divine authority and human moral accountability. The study contributes to Qur’anic exegesis by highlighting methodological flexibility in interpreting Qasam, though it is limited to these two tafsirs.